Introducing a Model for Analyzing the Possibilities of Power, Help and Control - Björn Kraus (Social Work & Society, 2014)
When looking at questions about the own objectives and the way of reaching them legitimately, professional social work always has to ask in the first place, if she can reach these objectives at all. This article concretizes this issue by discussing, which form of "power" actually can be granted to skilled social workers. Especially in settings, where skilled workers aim at promoting individual and/or social change, this question is inevitable. In these cases, the experts' power to exert influence has to be deliberated to the same extent than the power of relevant protagonists and systems. This paper deals with the fundamental question, what can be described with the term "power" at all. Therefore, it focuses neither the existence and distribution nor the normative appraisal of power, but the question, whether power always is a construction performed by the affected persons or if there are forms of power, which could take effect independently from the affected person's own will.  There will be a discussion about the potentials and limits of professional social workers and their power to help and control their addressees on the daily level of interaction from an epistemological point of view.